Optische Antennen aus Al und Au: Anregungskonzepte und Einfluss der Oxidation - Schwab, Patrick (KIT Scientific Publishing, 2016)
Optical antennas are metallic nanostructures showing a resonant behaviour which can be tuned at wish. In this work, optical antennas from aluminum and gold are fabricated, optically characterized and investigated numerically by FDTD methods. Aluminum allows resonances in the UV while it forms an oxide layer in air which alters the antenna response. For the first time, the results from a local electrial excitation of nanoplasmonic structures via STM is presented.